2019
DOI: 10.21608/ejnf.2019.75841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Ginger Powder or Ginger Oil on Productive Performance of Ewes During Lactation Period

Abstract: his experiment was carried out at Research Station of Maryout belonging to Desert Research Center to assess the effect of ginger forms (Zingiber officinale) on productive performance, rumen and blood parameters of Barki ewes. Forty Barki ewes at last pregnant stage, aged 3-4 year and average weighed 40.47 kg ± 0.99, were fed concentrate mixture and alfalfa hay (as traditional ration) and divided into four equal groups. 1 st group (T1) fed traditional ration without any supplementation as control group, the 2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…At the experimental endpoint, total protein concentration in all treated groups displayed a significant increase (p≤0.05) in comparing to control group, while no important differences were recorded between T3 and T4. Observed elevation in blood protein concentrations in the T3 and T4 groups agreed with Al-Dain and Jarjeis [18], Al-Azazi et al [19], and Abo Bakr [20], who observed statistically important increases (P<0.05) in total protein levels after the administration of ginger powder. The observed elevation in blood protein levels in the second group may be attributed to its capacity to stimulate nutrient absorption from the intestine, including vital amino acids, and enhance the efficiency of the digestive system.…”
Section: Resultssupporting
confidence: 88%
“…At the experimental endpoint, total protein concentration in all treated groups displayed a significant increase (p≤0.05) in comparing to control group, while no important differences were recorded between T3 and T4. Observed elevation in blood protein concentrations in the T3 and T4 groups agreed with Al-Dain and Jarjeis [18], Al-Azazi et al [19], and Abo Bakr [20], who observed statistically important increases (P<0.05) in total protein levels after the administration of ginger powder. The observed elevation in blood protein levels in the second group may be attributed to its capacity to stimulate nutrient absorption from the intestine, including vital amino acids, and enhance the efficiency of the digestive system.…”
Section: Resultssupporting
confidence: 88%
“…This aligns with findings from previous research on sheep, where the addition of ginger powder and oil resulted in a significant elevation of IgG concentration. Such effects can be attributed to the beneficial alterations induced by medicinal aromatic plants in the duodenal mucosa, ultimately enhancing immune function (Bakr 2019 ).…”
Section: Discussionmentioning
confidence: 99%